Pembelajaran Berdiferensiasi Solusi Tepat Dalam Meningkatkan Kemampuan Siswa di SDN 01 Tanjung Paku - Cindi Fadillah Sari; Nurhaliza; Nila Putri Sari; Putri Muliya; Dina Dahliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The learning process in primary schools is often faced with the problem of differences in students' abilities, interests and learning styles. This causes some students to have difficulty following lessons optimally if learning is carried out uniformly. This study aims to determine the effectiveness of the application of differentiated learning in improving students' learning abilities at SDN 01 Tanjung Paku. with qualitative and quantitative approaches. The research was conducted in two cycles with the stages of planning, action implementation, observation, and reflection. Data were collected through observation, learning outcome tests, and interviews. The results of the study show that the implementation of differentiated learning is significantly able to encourage students to be more active in learning and achieve better results every cycle.